Lercanidipine in the Management of Hypertension: An Update - Grassi, Guido (J Pharmacol Pharmacother, 2017)
Calcium channel blockers (CCBs), particularly dihydropyridine-CCBs, (DHP-CCBs), have an established role in antihypertensive therapy, either as monotherapy or in combination with other antihypertensive drugs. Two hundred and fifty-one papers published in PubMed in English between January 1, 1990, and October 31, 2016, were identified using the keyword “lercanidipine.” Lercanidipine is a lipophilic third-generation DHP-CCB, characterized by high vascular selectivity and persistence in the smooth muscle cell membranes. Lercanidipine is devoid of sympathetic activation, and unlike the first and second generation of DHP-CCBs, it dilates both the afferent and the efferent glomerular arteries, while preserving the intraglomerular pressure. In addition, lercanidipine prevents renal damage induced by angiotensin II and demonstrates anti-inflammatory, antioxidant, and anti-atherogenic properties through an increasing bioavailability of endothelial nitric oxide. It is associated with a regression of microvascular structural modifications in hypertensive patients. The efficacy of lercanidipine has been demonstrated in patients with different degrees of hypertension, in the young and elderly and in patients with isolated systolic hypertension. In patients with diabetes and renal impairment, lercanidipine displays a renal protection with a significant decrease of microalbuminuria and improvement of creatinine clearance. Lercanidipine is well tolerated and is associated with a very low rate of adverse events, particularly ankle edema, compared with amlodipine and nifedipine. In conclusion, lercanidipine produces a sustained blood pressure-lowering activity with a high rate of responder/normalized patients, associated with a favorable tolerability profile.